Chat in the Hat: A Portable Interpreter for Sign Language Users - Berke, Larwan; Thies, Bill; Bragg, Danielle (ASSETS 2020, 2020)
Many Deaf and Hard-of-Hearing (DHH) individuals rely on sign language interpreting to communicate with hearing peers. If on-site interpreting is not available, DHH individuals may use remote interpreting over a smartphone video-call. However, this solution requires the DHH individual to give up either 1) the use of one signing hand by holding the smartphone or 2) their ability to multitask and move around by propping the smartphone up in a fixed location. We explore this problem within the context of the workplace, and present a prototype hands-free device using augmented reality glasses with a hat-mounted fisheye camera and mic/speaker. To explore the validity of our design, we conducted 1) a video interpretability experiment, and 2) a user study with 18 participants (9 DHH, 9 hearing) in a workplace environment. Our results suggest that a hands-free device can support accurate interpretation while enhancing personal interactions.